Establishment of a C57BL/6 Mandibular Critical-Size Bone Defect Model. Issue 7 (October 2021) - Yu, Fei; Liu, Lu; Xia, Lunguo; Fang, Bing
Abstract : Purpose: The goal of this study was to identify bone defects of critical size in C57BL/6 mouse mandibles. Materials and Methods: Twenty-four male mice were included in this study. All mice underwent surgeries on their left mandibles. Mandibular defects of 1.0 mm (n = 8), 1.6 mm (n = 8), and 2.3 mm (n = 8) were created. For the investigation of bone healing after an 8-week period, micro-computed tomography scans and histomorphology were performed. Results: Mandibular bone nonunions were seen 0/8 in the 1.0-mm group, 6/8 in the 1.6-mm group, and 8/8 in the 2.3-mm group. The outcome of micro-computed tomography showed that, after 8 weeks, the bone mineral density and the bone volume to total volume ratio were significantly different among the 3 groups. The defect gaps in the nonunion 1.6- and 2.3-mm groups were filled with connective tissue, and no obvious bone formation was found. Additionally, in quantitative analysis, according to the new bone fill calculations, the percentages were 91.85% ± 8.03% in the 1.0-mm group, 59.84% ± 20.60% in the 1.6-mm group, and 15.36% ± 8.28% in the 2.3-mm group, which indicated statistically significantly lower defect healing in the 2.3-mm group. Conclusions: The creation of 2.3-mm mandibular defects produces osseous nonunion in C57BL/6 mice.